Money also is sunny in a retiree's world: Financial incentives and work after retirement - Svenja Lorenz; Thomas Zwick (Journal for Labour Market Research, 2021)
This paper assesses the impact of financial incentives on working after retirement. The empirical analysis is based on a large administrative individual career data set that includes information about 2% of all German employees subject to social security or in marginal employment until age 67 and their employers in the period 1975-2014. We use the classical labor supply model and differentiate between the impact of (potential) labor and non-labor (pension entitlements) income. A Heckman-type two step selection model corrects for endogeneity. We show that labor income has a positive and non-labor income a negative impact on the decision to work after retirement. Especially individuals who can substantially increase their earnings in comparison to their pension entitlements accordingly have a higher probability to work. Men are more attracted by labor earnings incentives than women. Also individuals who work until retirement are easier attracted to work after retirement by higher labor income than those with gaps between employment exit and retirement. Our results allow the calculation of the impact of changes in taxes on labor and non-labor income and changes in earnings offers by employers on work after retirement for different demographic groups.
Keywords: J14; J22; J26; 330; Work after retirement; Financial incentives; Labor and non-labor income